MANAJEMEN PENANGANAN MASTITIS PADA SAPI PERAH DI UPTD BPBPTDK DINAS PERTANIAN DI KABUPATEN SLEMAN - , DIKA SATRIA N S P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Field work practice been carried on for 6 days from 31 March to 5 April 2014 date. Methods to follow directly in UPTD BPBPTDK activities, a survey of the data - existing data and interviews with the veterinarian in charge of the farm. Activity is observed when the street vendors during milking, the cows in the bathed beforehand, especially the udder - should be clean and dry. Cages in the clear of dirt and food scraps. Various tools milking prepared, such as milk cans, ropes, buckets and cooking oil are in need when milking. Data obtained were 36 dairy cows that are in UPTD BPBPTDK 13 cows mastitis in last 3 years. Data from January 2010 to March 2014, the data showed that the affected dairy cow mastitis in the farms has decreased from 5 cases to 4 cases year. Sign - a sign of mastitis in the form of swelling and inflammation in the udder, cow's milk is changing its viscosity, milk from the udder that tested positive for the presence of mastitis showed wad. Treatment is carried out in UPTD BPBPTDK is by injecting antibiotics such as penicillin, intra-mammary oxytral much as 15ml morning and evening, for 3 consecutive days - helped. Milk milking cows injected antibiotics are not sold or consumed and only in afkir. Field work results can be concluded treatment of mastitis in UPTD BPBPTDK has fulfilled handling procedures.